Determining fair value and maximum price in corporate acquisition (case study: Palm Oil Industry) - Gunarta, I K; Alexander, G. (IPTEK Journal of Proceedings Series, 2018)
Acquisition is an act of taking over, in which negotiation may occur. Acquirer values target to determine the purchase price, based on existing condition of the target. This paper values the target with income approach on perspective of the acquirer. The approach applies financial model, estimating future income and cost of the target unto defined period. Net Present Value in free cash flow through the end of projected year is reflected as target value. On the other hand, maximum price acts as regards of the acquirer to point out the highest amount it could afford, yet still attaining positive return from the acquisition. This valuation is conducted in palm oil industry. Thus, the income and cost estimated are in regards to income and cost from oil palm plantation and palm oil mill. Value of the target is Rp. 249,518,452,138.67. Â The maximum purchase price applies similar cash flow to valuation, in addition to the expected purchase price in outflow component. Internal Rate of Return generated from this cash flow, in which is slightly above the required return, has the price as the maximum purchase price. It is accounted at Rp. 220,726,834,579.33.